"They haven't asked me. I haven't told them either": fertility plan discussions between women living with HIV and healthcare providers in western Ethiopia - Tesfaye Regassa Feyissa; Melissa L. Harris; Deborah Loxton (BMC, 2020)
Abstract Background Despite the importance of women living with HIV (WLHIV) engaging in fertility plan discussions with their healthcare providers (HCPs), little research exists. This study explored perceptions surrounding fertility plan discussions between WLHIV and their HCPs in western Ethiopia, from the perspectives of both women and providers. Methods Thirty-one interviews (27 with WLHIV and 4 with HCPs) were conducted at four healthcare facilities in western Ethiopia in 2018. Data were transcribed verbatim and translated into English. Codes and themes were identified using inductive thematic analysis. Results There was a discordance between HCPs and WLHIV's perception regarding the delivery of fertility plan discussions. Only nine of the 27 WLHIV reported they had discussed their personal fertility plans with their HCPs. When discussions did occur, safer conception and contraceptive use were the primary focus. Referrals to mother support groups, adherence counsellors as well as family planning clinics (where they can access reproductive counselling) facilitated fertility discussions. However, lack of initiating discussions by either HCPs or women, high client load and insufficient staffing, and a poor referral system were barriers to discussing fertility plans. Where discussions did occur, barriers to good quality interactions were: (a) lack of recognizing women's fertility needs; (b) a lack of time and being overworked; (c) mismatched fertility desire among couples; (d) non-disclosure of HIV-positive status to a partner; (e) poor partner involvement; (f) fear of repercussions of disclosing fertility desires to a HCP; and (g) HCPs fear of seroconversion. Conclusions Our findings highlight the need for policies and guidelines to support fertility plan discussions. Training of HCPs, provision of non-judgmental and client-centered fertility counselling, improving integration of services along with increased human resources are crucial to counselling provision. Enhancing partner involvement, and supporting and training mother support groups and adherence counsellors in providing fertility plan discussions are crucial to improving safer conception and effective contraceptive use, which helps in having healthy babies and reducing HIV transmission.